The Combination of Radiotherapy With Immunotherapy and Potential Predictive Biomarkers for Treatment of Non-Small Cell Lung Cancer Patients - Meng, Lu; Xu, Jianfang; Ye, Ying; Wang, Yingying; Luo, Shilan; Gong, Xiaomei (Frontiers in Immunology, 2021)
Radiotherapy is an effective local treatment modality of NSCLC in various stages. Its capabilities of eliminating tumor cells by inducing double strand DNA (dsDNA) damage and modulating anti-tumor immune response in both irradiated and non-irradiated sites have been elucidated. The novel ICIs therapy has brought hope to patients resistant to traditional treatment methods including radiotherapy. Integration of radiotherapy with immunotherapy has shown improved efficacy to control tumor progression as well as prolonged survival in NSCLC. Biomarkers which help choose the most effective treatment modality for individuals and avoid unnecessary toxicities caused by ineffective treatment are in urgent needs. This review summarized the effects of radiation in tumor immune microenvironment and the mechanisms involved. Outcomes of multiple clinical trials investigating immuno-radiotherapy were also discussed here. Furthermore, we outlined the emerging biomarkers for efficacy of ICIs as well as radiation therapy and discussed their predictive value in NSCLC patients.